Over a million students use our free study notes to help them with their homework
1) X2 +2Y2= 182) X - Y = 3Rearrange 2) in the form X=3-Y then substitute in to 1); (3-y)2+2Y2=18, this is your new equation 39+3Y+3Y+Y2+2Y...
0.057 x 15 = 0.855 total = 15 + 0.988 = 15.855
∫dy/dx = ∫6x^2 - 3x + 4y = (6/3)x^3 - ( 3/2)x^2 + 4x + cLet y = 14 and x = 214 = 2(2^3) - (3/2)(x^2) + 4(2) + c14 = 2(8) - (3/2)(4) + 4(2) + c14 = 16 - 6 + 8 + c14 = 18 + cc = -4therefore:y = 2x^3 - (3/2...
So there are 15 marbles in total (5 + 7 + 3) The probability of the first marble will be the number of blue marbles / total number of marblesTherefore, you do 5/15 = 1/3 Then for the second marble you do ...
First of all you need to spot a way we can add or subtract these two equations together so that we can get rid of one of the terms. This is easily spotted by writing the equations like so:2x - y ...
←
635
636
637
638
639
→
Internet Safety
Payment Security
Cyber
Essentials